2022
DOI: 10.3390/microorganisms10091698
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Regulators of G-Protein Signaling Genes in Leptographium qinlingensis and Expression Levels of Three RGSs in Response to Different Terpenoids

Abstract: Leptographium qinlingensis is a bark beetle-vectored pine pathogen in the Chinese white pine beetle (Dendroctonus armandi) epidemic in Northwest China. L. qinlingensis colonizes pines despite the trees’ massive oleoresin terpenoid defenses. Regulators of G-protein signaling (RGS) proteins modulate heterotrimeric G-protein signaling negatively and play multiple roles in the growth, asexual development, and pathogenicity of fungi. In this study, we have identified three L. qinlingensis RGS genes, and the phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Ophiostomatoid fungi are a food source for nematodes, that require the participation and regulation of multiple genes [7,33,34]. Expression of Ypt gene was upregulated in response to PWNs.…”
Section: Discussionmentioning
confidence: 99%
“…Ophiostomatoid fungi are a food source for nematodes, that require the participation and regulation of multiple genes [7,33,34]. Expression of Ypt gene was upregulated in response to PWNs.…”
Section: Discussionmentioning
confidence: 99%
“…To further validate the selected pathogenicity gene, attempts were made to standardize the RNAi-based approach during L. qinlingensis pathogenesis. Since our earlier study confirmed that FlbA plays a role in the growth and pathogenicity of L. qinlingensis [ 4 ], functional analysis of the FlbA gene has been selected for the RNAi approach using the fungal transformation vector pSilent-1 through Agrobacterium -mediated transformation (ATMT) and achieved knockdown of the target genes.…”
Section: Discussionmentioning
confidence: 99%
“…It assumes a crucial ecological and societal responsibility in water and soil conservation, thus wielding a significant impact on the local economy and ecology [ 2 ]. However, a rapid, widespread decline in Chinese white pine ( P. armandii ) has been brought on by an interaction biological complex (CWPB-Lq complex) that is formed of the Chinese white pine beetle ( Dendroctonus armandi , CWPB) and the ascomycetes fungus ( Leptographium qinlingensis , Lq) [ 3 , 4 , 5 ]. The activities of L. qinlingensis culminate in disruptions of nutrient and water metabolism, eventually leading to the demise of host trees due to the destruction of resin-producing cells and the obstruction of resin canals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations